Plays : Second Series - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Plays: Second Series" by John Galsworthy is a collection of dramatic works written during the early 20th century. This series includes several plays that tackle complex themes involving family dynamics, social issues, and moral dilemmas, particularly focusing on the upper-middle-class British society of the time. The central play in this series, "The Eldest Son," revolves around the struggles faced by the Cheshire family, particularly their eldest son Bill, as he navigates familial expectations and personal entanglements. The opening of "The Eldest Son" introduces us to the Cheshire family during a gathering at their country house, where a sense of tension pervades the atmosphere as various family members interact with one another. Through their dialogues, we learn about Bill's complicated relationship with both his family and his love interest, Freda, who is also the family's maid. The characters discuss social proprieties and the implications of love and duty, setting the stage for conflict as Bill contemplates his place in the family amidst financial pressures and romantic obligations. This portion effectively highlights the underlying themes of class distinction, loyalty, and the weight of societal expectations that are likely to unfold throughout the play. (This is an automatically generated summary.)
The eldest son -- The little dream -- Justice.
Release date is 2004-09-26
Produced by David Widger
Keywords: England -- Drama